pH Neutralization of Acid Mine Drainage Using Open Limestone Channel with Addition of Fly Ash and Silica Sand on Laboratory Scale Testing - Rizky Ananda; Rusli HAR; Heri Prabowo; Harizona Aulia Rahman (Departemen Teknik Pertambangan FT UNP, 2024)
This research aims to neutralize the pH of acid mine drainage using a passive open limestone channel method using limestone as a neutralizing agent, which is then modified by adding other test materials such as fly ash and silica sand. This test will be carried out through three repetitions which will later be called the AA-0 Combination, AA-1 Combination, and AA-3 Combination. The pH value of the acid mine drainage before the test was 3.75 and after the test was carried out, the final pH combination AA-0 was 7.39; The final pH of the AA-1 combination was 7.3; and AA-2 Combination The final pH is 7.21.